Viral Hepatitis and Hepatocellular Carcinoma: State of the Art - Toofan Datfar (MDPI AG, 2021)
Viral hepatitis is one of the main causes leading to hepatocellular carcinoma (HCC). The continued rise in incidence of HCC suggests additional factors following infection may be involved. This review examines recent studies investigating the molecular mechanisms of chronic hepatitis and its association with hepatocarcinogenesis. Hepatitis B virus patients with genotype C display an aggressive disease course leading to HCC more than other genotypes. Furthermore, hepatitis B excretory antigen (HBeAg) seems to be a more sensitive predictive tumor marker exhibiting a six-fold higher relative risk in patients with positive HBsAg and HBeAg than those with HBsAg only. Single or combined mutations of viral genome can predict HCC development in up to 80% of patients. Several mutations in HBx-gene are related with higher HCC incidence. Overexpression of the core protein in HCV leads to hepatocellular lipid accumulation associated with oncogenesis. Reduced number and decreased functionality of natural killer cells in chronic HCV individuals dysregulate their surveillance function in tumor and viral cells resulting in HCC. Furthermore, high T-cell immunoglobulin and mucin 3 levels supress CD8+ T-cells, which lead to immunological dysregulation. Hepatitis D promotes HCC development indirectly via modifications to innate immunity, epigenetic alterations and production of reactive oxygen species with the LHDAg being the most highly associated with HCC development. Summarizing the results, HBV and HCV infection represent the most associated forms of viral hepatitis causing HCC. Further studies are warranted to further improve the prediction of high-risk patients and development of targeted therapeutics preventing the transition from hepatic inflammation–fibrosis to cancer.